Microbiological predictors of clinical outcomes of autospongious osteoplasty in patients with gunshot fractures and bone tissue defects - Lytvyniuk, Oleksandr; Fishchenko, Volodymyr (ScienceRise: Medical Science, 2025)
The effectiveness of bone grafting depends not only on the size of the defect or the type of osteoplastic material used, but also on the microbial spectrum of the wound, the level of bacterial load, and the presence of biofilm. Objective. To assess the condition of wound microbiocenosis in gunshot fractures of long bones with bone tissue defects and its role in predicting the clinical outcome of autospongious osteoplasty. Materials and Methods. This study analyzed the results of bacteriological examination of wound contents and clinical indicators of autospongious osteoplasty in 40 patients with gunshot fractures of long bones accompanied by bone tissue defects. Clinical outcomes were assessed using the modified Neer–Grantham–Shelton 100-point scale. Bacteriological testing was performed according to standard protocols. Statistical analysis was conducted using IBM SPSS Statistics 27.0.1, with a significance level set at p≤0.05. Results. Excellent outcomes of autospongious osteoplasty were observed in 4 (10.0 %) patients, good in 11 (27.5 %), satisfactory in 17 (42.5 %), and poor in 8 (20.0 %). The analysis of the microbial species composition revealed significantly worse outcomes in cases of wound contamination with gram-negative flora (τ=–0.32, p=0.004), particularly members of the Enterobacteriaceae family (τ=–0.26, p=0.02), including Klebsiella pneumoniae (τ=–0.22, p=0.04), ESKAPE group pathogens (τ=-0,35, р=0,002). Conversely, identification of Bacillus species was associated with significantly higher odds of achieving excellent clinical outcomes (OR=51.00, CI (3.22-808.36), p=0.001). Conclusion. Monitoring the state of the wound microbiocenosis in patients with gunshot fractures and bone tissue defects is of both diagnostic and prognostic value in determining the clinical success of autologous bone grafting